Optimization of Indonesian Pineapple Exports to Japan by Utilizing The Indonesia – Japan Economic Partnership Agreement (IJEPA) - Ariela, Demarsya Putri (Jurnal Multidisiplin Indonesia, 2024)
This study discusses the optimization of Indonesia's pineapple exports to Japan by leveraging the Indonesia-Japan Economic Partnership Agreement (IJEPA). Although Indonesia is the world's second-largest pineapple producer and Japan is one of the largest pineapple importers, Indonesia's pineapple exports to Japan are still ranked sixth, below five other competing countries. This research aims to identify factors that can enhance the effectiveness of utilizing the IJEPA in Indonesia's pineapple exports to Japan. This study employs a quantitative method by applying RCA analysis to measure comparative advantages in pineapple production, ECI analysis to evaluate export competitiveness based on product quality, price, services, marketing, production efficiency, and ease of doing business, and EPD analysis to evaluate export product performance based on market share position. The results of this research are expected to provide a deeper understanding of the utilization of the IJEPA so that exporters can optimize Indonesia's pineapple export volume to Japan. Additionally, it is hoped that Indonesian businesses can effectively utilize this agreement and achieve greater success in entering the Japanese pineapple market..